Prenominal relative clauses in Ethiopian languages: From inside and from outside - Tong Wu (Studies in African Linguistics)
The main objective of this data-oriented study is to give a synchronic typological overview of Ethiopian prenominal relative clauses, both from the inside and from the outside. By “inside”, I mean to compare prenominal relative clauses in the Ethiopian area in order to show how they are different from and/or similar to each other. By “outside”, I extend the comparison to beyond Ethiopian languages and include other African languages with or without prenominal relative clauses and languages from elsewhere with prenominal relative clauses. These comparisons will show to what extent Ethiopian prenominal relative clauses are typologically marked or ordinary. However, the inside comparison will be given more attention. Furthermore, synchronic comparison naturally leads us to questions concerning language evolution and language contact. These questions have always been in the center of studies of the Ethiopian Language Area and will be discussed here.